Functional and radiological outcome of expert tibia nailing in proximal tibia fractures - Kadam, Rahul; Jadhav, Ashutosh Ajit; Chaallani, Abhay; Dagar, Preetam Singh; Pestonji, Jehangir Malcom (International Journal of Research in Orthopaedics, 2018)
Background: Previously treatment of choice for proximal tibia fracture was internal fixation by plate. Presently, expert tibia nail is widely used in treating proximal tibia fracture. Expert tibia nailing system has features like multi directional locking options in the distal and proximal part of the nail, in addition to the standard static and dynamic locking options present in IMIL Nail. Purpose of study is to evaluate the outcome of expert tibia nail in proximal tibia fracture. Methods: We retrospectively, reviewed thirty patients having proximal tibia fracture with age more than 18 years treated with expert tibia nail and were followed up averagely for 12 months between May2016 to May2018. All patients were compared in terms of intraoperative and postoperative parameters and functionally assessed using the Johner and Wruchs criteria at 3 weeks, 3 months, 6 months and 12 months. Results: Functional outcome was measured by Johner and Wruhs criteria of 30 patients showed 20 excellent, 8 good, 2 patients had fair results. Average time unprotected full weight bearing walking was 7.2 weeks. Average time taken for radiological union was 18.2 weeks. Conclusions: Expert tibial Interlocking Nail is good treatment option for proximal tibia fracture.